THE INFLUENCE OF QUALITY INFORMATION AND REPUTATION OF TIX ID APPLICATION TOWARD THE INTEREST OF PURCHASE TICKETS ONLINE IN XXI CINEMA CIPUTRA SERAYA MALL PEKANBARU CITY - Hadion Wijoyo; Septyani Larosa Marpaung (Jurnal Suluh Pendidikan, 2020)
The aim of this study has shawn that the quality of information and reputation TIX ID application toward of purchase tickets online interest in cinema XX1 Mall Ciputera Seraya Pekanbaru City. The independent factors in this study are quality information and reputation of application. The dependent factor is purchase interest. The subject of this research are user of TIX ID in cinema XXI Mall Ciputera Seraya Pekanbaru City. This research took 100 user as samples. The technique of data collection was accidental sampling. The instrument of data collection is questionaire method. In this research the researcher was used multiple regression analysis. The result has shawn that the quality of information affect of purchase interest. The reputation Tix Id application affect to purchase interest. the result of test explained how all independent variables affect the dependent variables. Result of multicollity show that R² results are 56% can explain how all independent variables affect the dependent variables. whereas the remaining 44% were described by other unexamined variables in this study